Оцінка ролі базисної терапії в розвитку ендотеліальної дисфункції у дітей, хворих на бронхіальну астму = The role of asthma's basic therapy in the development of endothelial dysfunction in children - Veronika M. Dudnyk; Katerina V. Khromykh (Kazimierz Wielki University, 2015)
Dudnik V M, Khromykh K V. Оцінка ролі базисної терапії в розвитку ендотеліальної дисфункції у дітей, хворих на бронхіальну астму = The role of asthma's basic therapy in the development of endothelial dysfunction in children. Journal of Education, Health and Sport. 2015;5(2):45-52. ISSN 2391-8306. DOI: 10.5281/zenodo.14934 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A45-52 https://pbn.nauka.gov.pl/works/534655 http://dx.doi.org/10.5281/zenodo.14934 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.     УДК 616.248 - 053:611.018.74:616 - 008.6   ОЦІНКА РОЛІ БАЗИСНОЇ ТЕРАПІЇ В РОЗВИТКУ ЕНДОТЕЛІАЛЬНОЇ ДИСФУНКЦІЇ У ДІТЕЙ, ХВОРИХ НА БРОНХІАЛЬНУ АСТМУ   THE ROLE OF ASTHMA'S BASIC THERAPY IN THE DEVELOPMENT OF ENDOTHELIAL DYSFUNCTION IN CHILDREN   В.М. Дудник, К.В. Хромих VM Dudnik, KV Khromykh   Вінницький національний медичний університет ім. М.І. Пирогова, кафедра педіатрії № 2 Pirogov Vinnitsa National Medical University, Pediatrics Department № 2   Резюме   Мета роботи - оцінка базисної протизапальної терапії інгаляційними глюкокортикоїдами в розвитку ендотеліальної дисфункції у дітей, хворих на бронхіальну астму. Матеріали та методи. Комплексно обстежено 224 дитини, хворі на БА, віком 6 - 17 років, із визначенням гомоцистеїну та судинного ендотеліального фактора росту. В якості контрольної групи було обстежено 40 здорових дітей. Результати. Встановлено, що вірогідність виникнення небажаних ефектів найвища при застосуванні монотерапії ІГК (OR 8,889; 95 % CI 4,803 - 16,449) та комбінованій терапії із кромонами (OR 1,111; 95 % CI1,051 - 2,734). Визначено, що чинниками ризику зростання вмісту гомоцистеїну більше 17,36 (11,3 - 24,5) мкмоль/л та VEGF вище 431,66 (238,04 - 658,09) пг/мл в сироватці крові дітей, хворих на БА були застосування ДАІ без доставочного пристрою та збільшення дози ІГК.   Ключові слова: бронхіальна астма, діти, ендотеліальна дисфункція.   Abstract   Purpose - estimation of basic anti-inflammatory therapy with inhaled glucocorticoids in the development of endothelial dysfunction in children with asthma. Materials and methods. Comprehensively examined 224 children with asthma, aged 6 - 17 years, with determination of homocysteine and vascular endothelial growth factor. 40 healthy children were examined as a control group. Results. Established that the likelihood of adverse effects when using the highest GCI monotherapy (OR 8,889; 95% CI 4,803 - 16,449) and combination therapy with mast cell membranes stabilizeres (OR 1,111; 95% CI1,051 - 2,734). Determined that the risk factors increase homocysteine than 17.36 (11.3 - 24.5) mmol / l and VEGF above 431.66 (238.04 - 658.09) pg / ml in serum of children with asthma were using of doses aerosol inhalators without conveying device and without increasing of IGC dose.   Key words: asthma, children, endothelial dysfunction.